Pengaruh Gradien 40o/oo Terhadap Jumlah LRV Yang Ditarik Kereta Penolong untuk Menghindari Terjadinya Slip Pada LRT Jakarta - Fadli Irnanda Saputra Darmono; Ramon Trisno (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
LRT Jakarta is one of the train operators in Indonesia. Apart from the passenger train (LRV), the Jakarta LRT also has a helper train (MRV). At the Jakarta LRT, the MRV operation has to pass a very steep incline, namely a 40o/oo gradient. This can result in a high probability of slippage. Such an incident can be avoided if we know how much the adhesion pull of the tow cart and the total resistance of the tow cart. For that we need further calculations regarding the total resistance of the train to the adhesion tensile force. So that in this final project will produce the maximum number of trains that can be pulled by the locomotive so that no slip occurs. With quantitative methods, data collection and calculation / analysis, the expected results are obtained in this final report. So that it can be seen that the maximum MRV traction effort is 107 kN and the resistance by pulling 3 LRV is 99 kN. Slip occurs when the resistance exceeds maximum traction effort. So it can be concluded that the MRV can attract 3 LRV without any slip when on the 40o/oo gradient path.